The HUBUNGAN PELAKSANAAN PHBS DITATANAN SEKOLAH DENGAN KEJADIAN DIARE - Ariesta Mountia; Sutrisno Sutrisno; Yessie Christianto (MNJ (Mahakam Nursing Journal), 2021)
Patients with diarrhea will fall dehydration if not immediately saved 50-60% will die, particularly in East Kalimantan province in 2015 diarrhea incidence of children aged> 5 years as many as 50 872 people, two children of them died, while the data of diarrhea in the city of Samarinda 2016 in children aged 5-9 years there were 7758 patients , 3 of them died while in children aged 10-14 years there are 2741 patients (East Kalimantan Provincial Health Office, 2016). Efforts to reduce the incidence of diarrhea in children of school age to early prevention through the implementation of CHLB ditatanan school. This study aims to determine the relationship between the implementation of CHLB arranged school with the incidence of diarrhea at the elementary school country of 007 Samarinda Seberang. This research is a quantitative research with analytic observation design, using cross-sectional approach with retrospective cohort design. The results showed that respondents did not experience diarrhea in small percentage of respondents (5.6%) and almost (97.1%) had diarrhea. There are significant correlation between the implementation of CHLB arranged school with the incidence of diarrhea with p value = 0,000 <0,05. Keywords: CHLB, at school, diarrhea in children